Georgia : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2005)
The Poverty Reduction Strategy Papers (PRSPs) on Georgia review macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major sources of financing. The sustainability of high economic growth is a positive tendency in the economy of Georgia. The social and economic hardship in the country and a less favorable entrepreneurial environment forces people to search for a living outside Georgia. The main priority of the National Bank of Georgia (NBG) is to conduct the monetary and exchange rate policy oriented on price stability.